Pengembangan Evaluasi Pembelajaran Bahasa Arab Berbasis Penilaian Autentik Madrasah Tsanawiyah Miftahul Huda Madura - Fitriani, Namiyah; Zaman, Badrus; Imron, Mohammad (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This study aims to describe the implementation of authentic assessment in Arabic language learning at MTs Miftahul Huda Madura. Using a qualitative approach with a case study method, this research involved Arabic teachers and students as participants selected through purposive sampling techniques. Data were collected through participatory observation, in-depth interviews, and documentation studies of syllabi, lesson plans, and assessment instruments. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The results show that authentic assessment implementation covers three competency aspects: cognitive (using short- answer and essay tests), affective (through peer assessment and student journals), and psychomotor (using project and practice assessments). Supporting factors include enjoyable learning activities, availability of teaching aids, teacher and student readiness, and adequate time allocation. Meanwhile, inhibiting factors include student discipline issues, low Arabic language proficiency, and difficulties in reading and comprehending Arabic texts. This study provides an empirical model for implementing authentic assessment in madrasah contexts and offers practical recommendations for developing more holistic Arabic language learning evaluation systems.